PENGARUH KECERDASAN INTELEKTUAL, DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PELAKU USAHA KECIL DI KOTA BANDUNG - Harun Heri Trismiyanto; Iwan Ardiansyah (KarismaPro, 2021)
Future uncertainty that can occur in financial services companies is a risk that Small industries in the city of Bandung play a very important role and contribute to the economy in the city of Bandung and nationally. For this reason, it is necessary to have high performance so that it can compete both in the national market and in the global market.This study aims to identify external and internal factors that determine the influence of intellectual, intelligence and emotional intelligence on the performance of small business actors on handicraft products in Bandung City. Small industries are still constrained by various internal and external factors. Internal factors include aspects of human resources and capital, marketing and design, while external factors include market conditions, availability of raw materials and government policies.Types of data are secondary data obtained from various related literatures. The sample in this study amounted to 50 business actors.Small entrepreneurs must maintain the implementation of the important factors that determine the performance of their business, while still making improvements to the factors that are still not being implemented, in order to get better performance.Keywords: Intellectual and Emotional Intelligence on the Performance of Small Business Owners in Bandung